Dynamics of management practices in Eastern Europe: The case of Bulgaria - Emanuela Todeva (Journal for East European Management Studies, 1996)
This article provides a critical review of the Socialist Management System with a profile of management practices in the centrally planned economies in Eastern Europe. It draws on the work by Kornai and Chavance, exploring the economic reforms in Eastern Europe pre-1989 and the typical management behaviour in response to administrative changes in that time. The profile of the Socialist Management System is compared with the changes in management practices in the construction industry in Bulgaria in 1994-95. The comparative analysis includes two case studies - one state firm Metal Design, and one private firm Apolos - representing the changes in management under the pressure of market reforms. – – Der vorliegende Artikel gibt einen kritischen Überblick über das sozialistische Management-System anhand eines Profils der Management-Praktiken in den zentralen Planwirtschaften Osteuropas. Ausgehend von den Arbeiten von Kornai und Chavance werden die ökonomischen Reformen in Osteuropa vor 1989 und die typischen Verhaltensweisen des Managements gegenüber den administrativen Reformen dieser Zeit untersucht. Das Profil des sozialistischen Management-Systems wird verglichen mit den Management-Praktiken in der bulgarischen Bauindustrie in den Jahren 1994-95. Die vergleichende Analyse enthält zwei Fallstudien - die staatliche Firma Metal Design und die private Firma Apolos - die beispielhaft die Veränderungen im Management unter dem Druck der marktwirtschaftlichen Reformen aufzeigen.
Keywords: 650